تأثير الوحدات تدريبية مقترحة بطريقة( الستريتشينغ )الاستطالة العضلية على خاصية المرونة على لاعبين كرة القدم - بن أم هاني, وليد; محمدي, مبارك; د.شريفي, سليم (My University, 2021)
 العنوان : تأثير الوحدات التدريبية مقترحة بطريقة السترتشينغ الاستطالة العضلية على خاصية المرونة لدى لاعبي كرة القدم.  أهداف الدراسة : لقد حاولنا خلال هذا البحث إلى تحقيق جملة من الأهداف يمكن حصرها في :  معرفة تأثير الوحدات التدريبية المقترحة باستعمال تمارين الإطالة العضلية على خاصية المرونة  معرفة ما اذا كانت فروق ذات دلالة معنوية في صفة المرونة لدى المجموعتين الضابطة و التجريبية خلال التطبيق القبلي.  معرفة ما اذا كانت فروق ذات دلالة معنوية في صفة المرونة لدى المجموعتين الضابطة و التجريبية خلال التطبيق البعدي.  منهج الدراسة : كان من المفروض إتباع المنهج التجريبي ونظرا للظروف الصحية للبلاد ارتأينا استعمال المنهج التحليل المحتوى . إن المنهج في البحث العلمي يعني تلك الأسس والقواعد التي يتم رسمها من أجل بلوغ حقيقة ويقول (عمار بوحوش ومحمد ذنيبات ) " إنه الطريقة التي يتبعها الباحث في دراسته للمشكلة لاكتشاف الحقيقة" والمنهج البحث يختلف باختلاف المواضيع البحث ولهذا توجد عدة أنواع من المناهج العلمية .( بن قناب الحاج رسالة مقدمة لنيل شهادة دكتوراه في نظريات). ويعتبر المنهج التجريبي هو المنهج الوحيد الذي يمكنه الاختبار الحقيقي لفروض العلاقات الخاصة بالسبب أو الأثر (ومناهج التربية البدنية والرياضية 2006ص.211) ومن أكفأ وأنجح المناهج لاختبار صدق الفروض، وتحديد العلاقات بين المتغيرات،وتهيئة الأساس المقنع والأرضية القوية لاستخلاص الاستنتاجات السببية (مصطفى حسين باهي وآخرون: 2013ص.99) ويعرف المنهج التجريبي بمسميات عديدة الطريقة التجريبية أو السبب والنتيجة أو الطريقة المعملية. (مروان عبد المجيد إبراهيم: .137 ص2002 ،الأردن) وبما أن الدراسة تتناسب مع المنهج التجريبي كان من المفروض إتباعه في دراسة.  مجتمع و عينة الدراسة: توجهنا لنادي أمل بوسعادة الناشط في الرابطة المحترفة الجزائرية الثانية كان من المفروض تطبيق عليها دراسة كاملة لكن توقفنا بعد قياس للاختبار القبلي نظرا لانتشار وباء كورونا في بوسعادة توقف عملنا والتجأنا إلى طريقة تحليل المحتوى . يتكون المجتمع الأصلي للدراسة من 25 لاعب , وقسمة العينة إلى مجموعتين:  المجموعة التجريبية : وهي المجموعة التي كانت من المفروض أن تتعرض للمعالجة التجريبية من خلال التجربة الميدانية أو متغير المستقل لمعرفة تأثير هذا المتغير عليها تطبق عليها حيث بلغ قوامها 10 لاعب من نادي أمل بوسعادة u20  المجموعة الضابطة : وهي المجموعة التي كان من الفروض أن لا تتعرض للمعالجة التجريبية حيث تلقت تدريباتها بشكل عادى ونظرا لأهميتها تعتبر مصدرا من مصادر الصدق الداخلي للتجربة وتقدم هذه المجموعة فائدة كبيرة للباحث حيث تكون الفروق بين المجموعتين التجريبية والضابطة عن المتغير التجريبي الذي تعرضت له المجموعة التجريبية.و تضم 10لاعبين من النادي أمل بوسعادة u20.  أدوات جمع البيانات: الاختبارات البدنية: القياس هو علم وفن استخدام الأجهزة الحديثة، فإذا استطعت أن تقيس ما تتكلم عنه وتعبر عنه بالأرقام فإنك تعلم بعض الشيء عنه واذا لم تستطع أن تقيس ما تتكلم عنه بالأرقام فإنك لا تعلم عن الموضوع الذي تتكلم عنه.( https://www.training-fb.com/2018/02/sit-and-reach-test.html) لكي يتعرف المدرب على إمكانيات وقابليات اللاعب بشكل منفرد، والفريق بشكل جماعي،عليه إجراء اختبارات وقياسات للتعرف على هذه المستويات لأن هذه الاختبارات من الوسائل المهمة في تقويم اللاعبين والتعرف على مستوياتهم باستخدام الأساليب والوسائل والأجهزة المتطورة للوصول إلى نتائج دقيقة، ويعد الاختبار المؤشر الحقيقي لحالة التدريب (مستوى اللاعب) في مفردة أو عدة مفردات في كرة القدم، وهنا يتمكن المدرب أو القائم على الاختبار من معرف المستوى ومن خلاله يمكن وضع الحكم على المفردة قيد الاختبار، و هو الاستجابة الحقيقية من قبل اللاعب لحركات مقننة يتوجب أداؤها بأسلوب وطريقة محددة وذلك للوقوف على مستوى اللاعب في حالة معينة في كرة القدم.2  الاختبارات : 1- اختبار المرنة خلف الفخذ أسفل الظهر Sit and reach test : اختبار المرونة خلف الفخذ و أسفل الظهر لقياس قدرة المفاصل و العضلات على الوصول إلى أقصى مدى تشريحي. 2- اختبار مدى مرونة الجذع والرقبة:  الغرض من الاختبار: _ قياس مرونة الجذع والرقبة 3- اختبار ثني الجذع من الوقوف:  الغـرض من الاختبـار : قياس مدى مرونة الجذع والفخذ فى حركات الثنى للأمام من وضع الوقوف .  وبناء على نتائج الدراسات السابقة و المشابهة و التي توصلت الى مجملها على : - أفرزت نتائج المعالجة الإحصائية على عدم وجود فروق ذات دلالة إحصائية للاختبارين القبليين لكل من العينتين الضابطة والتجريبية في كل اختبارات المرونة. - وجود فروق ذات دلالة إحصائية للاختبارين البعديين لكل من العينتين الضابطة والتجريبية في كل الاختبارات مرونة ولصالح المجموعة التجريبية. - وجود فروق ذات دلالة إحصائية للاختبارين البعدي والقبلي للعينة التجريبية في كل اختبارات المرونة ولصالح الاختبار البعدي. - حققت المجموعة التجريبية زيادة معتبرة في جميع اختبارات المرونة . - نجاعة ونجاح البرنامج المقترح المبني على تمارين المرونة. يمكن التنبؤ بالنتائج التي كان من المفروض التوصل اليها في دراستنا بعد اتباع المنهج التجريبي مفادها وجود علاقة ترابطية بين التمديد العضلي و صفة المرونة .  اقتراحات و فرضيات مستقبلية: خلصنا إلى مجموعة من التوصيات وبعض الاقتراحات كما يلي : - ضرورة التركيز على إدماج تمارين وبرامج تطويرية قصد تحسين القدرة على المرونة لدى اللاعبين - إعطاء أهمية بالغة التمديد العضلي في كرة القدم في مرحلة الطفولة خاصة باعتبارها المرحلة الأساسية لترسيخ المرونة لدى اللاعبين . - تحسين القدرة على التمديدات العضلية قصد الوصول إلى تحسين المرونة .  Title: The effect of training units suggested by the elongation-stretching method Muscular strength on the flexibility of football players .  Study Objectives: During this research we have tried to achieve a set of objectives that can be summarized in: - Knowing the effect of the proposed training units using muscle lengthening on the flexibility. . Suggesting mixing static and dynamic stretching exercises during the warm-up process in football. - the effect of stretching exercises or muscle stretching exercises on many variables due to the lack of these studies in Arabic. - Attempting to touch new aspects that were not addressed by previous studies on the same subject. - Draw some results that can help trainers and educators in the optimal use of stretching exercises. _Through our study of the rationale and our perception of the nature of the problem, we have identified the following objectives:  Highlighting the effect of muscle lengthening on flexibility.  Highlighting the importance and role of the proposed training units in developing and improving flexibility.  Highlighting the importance of flexibility for soccer players  Slimming with the importance of muscle lengthening and flexibility and their role.  Enriching the knowledge side by identifying the types of stress and flexibility and ways to develop them  Study Methodology: It was supposed to follow the experimental method, and given the health conditions of the country, we decided to use the content analysis method. The method in scientific research means those foundations and rules that are drawn up in order to reach the truth. Ammar Bouhoush and Muhammad Thuneibat say, “It is the method that the researcher follows in his study of the problem to discover the truth, and the research method varies according to the different topics of the research, and for this there are several types of scientific methods.” Hajj Risala is an introduction to obtaining a doctorate degree in theories) The experimental method is the only method that can truly test the hypotheses of cause or effect relationships and( thephysical and sports education curricula 2006 p. 211) and one of the most efficient and successful approaches is to test the validity of the hypotheses, determine the relationships between variables, and prepare the foundation Masker and floor. The experimental method is known by many names, the experimental method, the cause and effect, or the laboratory method. (Marwan Abdul Majeed Ibrahim, 137. pg. 2002, Jordan) Since the study fits with the experimental method, it was supposed to be followed in a study.  Society and sample of the study: We went to AmalBousaada Club, the activist in the second Algerian professional league. It was supposed to apply a full study to it, but we stopped after measuring the tribal test due to the spread of the Corona epidemic in Bousaada. into two groups.  Experimental group: It is the group that was supposed to be subjected to experimental treatment through the field experiment or the independent variable to see the effect of this variable on it. It is applied to it, as it reached 10 players from AmalBousaada club u20:  The control group: It is the group that was supposed to not It is subjected to experimental treatment, as it received its training in a normal way, and due to its importance, it is considered a source of internal validity of the experiment.  Data collection tools: Physical tests :Measurement is the science and art of using modern devices. If you can measure what you are talking about and express it in numbers. You know a little about it, and if you cannot measure what you are talking about with numbers, then you do not know about the subject you are talking about. (https://www.trainingfb.com/2018/02/sit-and-reach-test.html) In order for the coach to recognize the capabilities and capabilities of the player individually, and the team collectively, he must conduct tests and measurements to identify these levels because these tests One of the important means in evaluating players and identifying their levels using advanced methods, means and devices to reach accurate results, and the test is the real indicator of the training status (the player’s level in a single or several vocabulary in football, and here the coach or the test-taker can identify the level and through it The judgment can be put on the individual under test, and it is the real response by the player. The movements are codified, which must be performed in a specific manner and method, in order to determine the level of the player in a certain situation in football.  Tests: 1-The sit and reach test: the test of flexibility behind the thigh and lower back to measure the ability of joints and muscles to reach the maximum anatomical extent. 2- Torso and neck flexibility test:  The purpose of the test : is to measure the flexibility of the trunk and neck 3-Trunk flexion test from standing:  The purpose of the test: To measure the flexibility of the trunk and thigh in forward flexion movements from a standing position.  And based on the results of previous and similar studies, which concluded in their entirety that: - The results of the statistical treatment revealed that there were no statistically significant differences for the two pre-tests for each of the control and experimental samples in all flexibility tests. - There are statistically significant differences for the two post-tests for each of the control and experimental samples in all flexible tests and in favor of the experimental group. - There are statistically significant differences for the post- and pre-tests of the experimental sample in all flexibility tests in favor of the post-test. - The experimental group achieved a significant increase in all flexibility tests. - The efficacy and success of the proposed program based on flexibility exercises. The results that were supposed to be reached in our study can be predicted after following the experimental method, that there is a correlation between muscle extension and flexibility.  Suggestions and future hypotheses: We concluded a set of recommendations and some suggestions as follows: _The need to focus on integrating developmental exercises and programs in order to improve the players' flexibility. _Giving great importance to muscle extension in football, especially in childhood. _As the basic stage to establish flexibility among the players. Improving the ability to stretch muscles in order to improve flexibility
Keywords: الوحدات التدريبية; السترتشينغ; الاستطالة العضلية; كرة القدم